Assessment of disease activity in Graves’ orbitopathy - Potvin, Arnaud R. G. G.; Lacraru, Ioana C.; Bisschop, Peter H.; de Win, Maartje M. L.; Eckstein, Anja K.; Saeed, Peerooz (Frontiers in Ophthalmology, 2025)
PurposeGraves’ orbitopathy (GO) is the most common extra-thyroidal manifestation of Graves’ disease (GD). Clinical disease activity and severity stage at the time of diagnosis are commonly used to determine the optimal treatment. There are still controversies regarding the “gold standard” for establishing disease activity. Although the clinical activity score (CAS) is the best evaluated parameter and therefore widely used, it lacks the ability to predict disease progression in all patients and response to anti-inflammatory treatment. Additional predictors are needed to select the optimal treatment for each patient.MethodsWe conducted a comprehensive review of the literature on activity assessment in GO.ResultsA large variety of parameters are used in studies to assess disease activity, most common clinical activity/severity scores, orbital imaging techniques, and serum biomarkers. CAS remains the best validated way for activity scoring. Other promising parameters, including specific MRI sequences (short tau inversion recovery, T2 mapping, and diffusion-weighted imaging sequences) and serological biomarkers [thyroid-stimulating immunoglobulin (TSI)/thyroid-stimulating hormone (TSH)-binding inhibitor immunoglobulin (TBII)], are starting to prove their utility in quantifying disease activity and in predicting the outcome of GO. TBII and TSI measurements’ cutoff values for prognostic statements are available for almost all routine test systems and should be used more systematically as biomarkers for GO.ConclusionsCAS is still considered the gold standard for assessing disease activity. Applied alone, CAS fails to predict disease progression in all patients. The future assessment is probably a combination of clinical, serological, and imaging measurements. The selection of treatment should be tailored to the manifestations and main treatment effects of the available drugs. Future studies will need to determine which parameters provide the best predictions for each drug class.